Using eye-tracking research to investigate language test validity and design. (July 2019) - Bax, Stephen; Chan, Sathena
Abstract: This paper reports on a recent study which used eye-tracking methodology to examine the cognitive validity of two level-specific English Proficiency Reading Tests (CEFR B2 and C1). Using a mixed-methods approach, the study investigated test takers' reading patterns on six item types using eye-tracking, a self-report checklist and stimulated recall interviews. Twenty L2 participants completed 30 items on a computer, with the Tobii X2 Eye Tracker recording their eye movements on screen. Immediately after they had completed each item type, they reported their reading processes by using a Reading Process Checklist. Eight students further participated in a stimulated recall interview while viewing video footage of their gaze patterns on the test. The findings indicate (1) the range of cognitive processes elicited by different reading item types at the two levels; and (2) the differences between stronger and weaker test takers' reading patterns on each item type. The implications of this study to reflect on some fundamental questions regarding the use of eye-tracking in language research are discussed. The paper concludes with recommendations for future research in these areas.